INCREASING CREATIVITY OF EARLY CHILDHOOD THROUGH ORIGAMI PLAYING ACTIVITIES - setiawati wati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
This study aims to improve the creativity of early childhood through origami playing in the At-Takwa  play group in Padasuka sub-district, Cimahi Tengah sub-district, Cimahi City. In accordance with the study, the research method used is a qualitative research method. The research subjects were early childhood groups playing At-Takwa Padasuka sub-district, Cimahi Tengah City district, Cimahi, totaling 10 children. Data collection techniques obtained through interviews, observation, and documentation. Data analysis techniques in this study are data reduction, data display and verification. Increased creativity of Early Childhood through origami playing activities characterized by 5 aspects of creativity include: (1). Children's ability to issue new ideas (2). New ideas or products (3). New combinations based on existing data (4). Idealis in working (5). Demonstrating independence. The results of the enhancement of the 5 aspects of creativity in the At-Takwa Cimahi Playgroup Children indicated by the achievement of scores on the categories of creativity development are as follows: Before the research actions from the pre-survey observations in the At-Takwa  play group Padasuka village Cimahi obtained the results of creativity development of children who have not Growing by 40%, Starting to Grow by 50% and Developing According to Expectations of 10% and final observations on the creativity of children in the At-Takwa  play group in Padasuka sub district Cimahi  showing an increase in the development of children's creativity according to Expectations by 60% and Developing Very Well 30%.